Respostas do milho à adubação com fósforo e zinco - De Souza, ECA; Coutinho, ELM; Natale, W.; Barbosa, J. C. (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 1998)
With the objective of evaluating the effects of phosphorus (0, 50, 100, 150 and 200 kg ha(-1) of P(2)O(5)) and zinc (0, 5, 10, 15 and 20 kg ha(-1) of Zn) fertilization in the maize crop, a field experiment was conducted on a Haplustox soil with 5 mg dm(3) of P and 0.39 mg dm(-3) of Zn (DTPA). From the results, it was observed that the fertilization with P and Zn resulted in significant increments of corn grain yield. The effect of P fertilization was higher than the fertilization with Zn. It was possible to obtain a production of grain up to 6,000 kg ha(-1) with P alone; higher yield than it was achieved only with both P and Zn fertilization. The maximum corn grain yield was associated with P contents in soil about 30 mg dm(-3). Phosphorus did not alter the contents of Zn in the leaves.

Com o objetivo de verificar os efeitos isolados e combinados da adubação com fósforo (0, 50, 100, 150 e 200 kg ha-1 de P2O5) e zinco (0, 5, 10, 15 e 20 kg ha-1 de Zn) na cultura do milho, conduziu-se um experimento num Latossolo Vermelho-Escuro textura média, com 5 mg dm-3 de P e 0,39 mg dm-3 de Zn (DTPA). Pelos resultados obtidos, vê-se que a adição de P e Zn aumentou significativamente a produção de grãos de milho. O efeito da adubação fosfatada foi mais pronunciado que o da adubação com Zn. Pôde-se obter produções de até 6.000 kg ha-1 utilizando-se somente o macronutriente; para produções acima deste valor, é necessário, além do P, a inclusão do Zn na adubação. A máxima produção de grãos esteve associada a uma concentração de P no solo de 30 mg dm-3. A adubação fosfatada não alterou significativamente as concentrações de Zn nas folhas.
Response of corn to phosphorus and zinc fertilization
Keywords: Zea mays; P-Zn interaction